Tantangan Pewirausaha di Bidang TI: Bagaimana Menghasilkan Keuntungan dari Ide? Studi Kasus Pada PT â€œIPSâ€ (Payment Gateway) - Lisanti, Yuliana (Bina Nusantara University, 2014)
It was not easy to start a business, let alone to run it. However, the spirit and ideas of the three founder of PT ?IPS? has successfully created an innovative business that is a payment gateway to help sellers and buyers to make purchases online. However, there is a major problem for many IT entrepreneurs faced by PT ?IPS? that is how to gain profit from the business. PT ?IPS? hopes to make a profit from the efforts undertaken By understanding customer behavior and how other business people can get profit from the business relating to technology, such as improving customer value, distinguishing between types of member and amenities, providing